How does livestock graze management affect woodland soil health? - Bastani, Maryam; Sadeghipour, Ahmad; Kamali, Nadia; Zarafshar, Mehrdad; Bazot, Stephane (Frontiers in Forests and Global Change, 2023)
Soil is the fundamental component of each terrestrial ecosystem, so the consequences of land management regime on soil health and productivity should be evaluated. To this end, the long term effects of livestock grazing management on soil health were studied in three land management systems of north-eastern Iran, comprising unlimited grazing, managed grazing, and a rangeland where grazing was prohibited. First, properties including pH, EC, bulk density and contents of phosphorus, potassium and calcium in soils subject to the three grazing management regimes were compared. Then, seasonal variations of organic carbon, total nitrogen, microbial respiration (BR and SIR), carbon and nitrogen of microbial biomass (MBC and MBN), fungal biomass and AMF (Arbuscular mycorrhizal fungi) spore density were studied at the three sites. Several soil stoichiometric microbial indicators were also compared. Soil phosphorus contents were found to drastically decline (by around 40%) in response to long term unlimited grazing, while soil acidity and bulk density slightly increased under that grazing regime, in comparison with managed-grazing and grazing-excluded rangelands. Season and grazing management had significant impacts on all the studied variables. Although soil nitrogen content increased, presumably due to livestock urine, organic carbon content and all the soil microbial variables declined in grazed sites, which were also the ones with lower plant cover. A higher AFM spore density was observed around the rhizosphere of Artemisia aucheri, the most frequent plant, in lands with unlimited grazing. Based on these results, managed grazing is strongly recommended rather than any kind of unlimited or continuous grazing.